2018
DOI: 10.1177/0961203318787037
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 1555 childhood-onset lupus in three groups based on distinct time intervals to disease diagnosis: a Brazilian multicenter study

Abstract: Objective The objective of this study was to compare demographic data, clinical/laboratorial features and disease activity at diagnosis in three different groups with distinct time intervals between onset of signs/symptoms and disease diagnosis. Methods A multicenter study was performed in 1555 childhood-onset systemic lupus erythematosus (American College of Rheumatology criteria) patients from 27 pediatric rheumatology services. Patients were divided into three childhood-onset systemic lupus erythematosus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 18 publications
0
19
0
4
Order By: Relevance
“…This was a retrospective multicenter study that included a database of 1697 cSLE patients included in the Brazilian cSLE Registry, from 27 Brazilian Pediatric Rheumatology centers, as previously reported. 9,10 One thousand and twenty-seven patients were excluded due to incomplete charts, incomplete data about 1997-ACR or 2019-EULAR/ ACR classification criteria or more than 5 years of disease duration. Therefore, a population of 670 cSLE was studied.…”
Section: Methodsmentioning
confidence: 99%
“…This was a retrospective multicenter study that included a database of 1697 cSLE patients included in the Brazilian cSLE Registry, from 27 Brazilian Pediatric Rheumatology centers, as previously reported. 9,10 One thousand and twenty-seven patients were excluded due to incomplete charts, incomplete data about 1997-ACR or 2019-EULAR/ ACR classification criteria or more than 5 years of disease duration. Therefore, a population of 670 cSLE was studied.…”
Section: Methodsmentioning
confidence: 99%
“…The Brazilian registry assessed 1533 cSLE patients based on three groups with different periods between the onset of signs/symptoms and the diagnosis. This study revealed cSLE patients infrequently had a shorter time interval to diagnosis (< 1 month) characterized by multisystemic, severe, and active conditions, whereas the majority of cSLE patients had a long-time interval (≥ 3 months) to diagnosis, with mild disease onset [ 21 ].…”
Section: Childhood-onset Systemic Lupus Erythematosus (Csle) Stratification and New Validated Classification Criteriamentioning
confidence: 99%
“…Individuals diagnosed with cSLE are at a higher risk of irreversible damage than their adult counterparts [24,25]. Timely diagnosis, earlier referral to sub-specialists, and aggressive management improve long-term outcomes, prevent organ failure, and increase survival in these patients [26][27][28][29]. A study conducted in the United States indicated that cSLE patients were less likely to present without delay if they lived in a poor density area for pediatric rheumatologists [28].…”
Section: Delays In Diagnosis Of Cslementioning
confidence: 99%
“…A retrospective cohort study in Brazil divided 1,555 cSLE patients recruited from 27 rheumatology services into three groups based on time to diagnosis: group A: short time interval (<one month), group B: intermediate time interval (one to three months), and group C: long time interval (>three months) [27].…”
Section: Delays In Diagnosis Of Cslementioning
confidence: 99%